Predicting protein-binding RNA nucleotides with consideration of binding partners. Issue 1 (June 2015) - Tuvshinjargal, Narankhuu; Lee, Wook; Park, Byungkyu; Han, Kyungsook
<x xml:space="preserve">Abstract</x> Highlights A method to predict protein-binding sites in RNA from sequence data alone is proposed. Protein-binding sites in RNA are predicted with consideration of protein in addition to RNA. This is the first sequence-based prediction of protein-binding sites in RNA at the nucleotide-level. The prediction method achieved an accuracy of 79.2% and MCC of 0.48 in independent testing.